Assessment of Prevention of Mother-to-Child Transmission HIV Services in the Bantey Meanchey Province in Cambodia. (July 2016) - Sau, Mealiny Sokun; Balamane, Maya; Lurie, Mark; Harwell, Joseph; Welle, Emily; Mean, Chhivun; Cu-Uvin, Susan
Background: Elimination of pediatric HIV requires a robust program for the prevention of mother-to-child transmission (PMTCT). The goal of this study was to assess the implementation of these services in Cambodia. Methods: This prospective study was conducted in Bantey Meanchey at 2 sites. Staff reviewed daily clinic and laboratory registration logs to gather data on PMTCT service access among antenatal women. Results: A total of 12 140 pregnant women received antenatal care. Only 4034 (33.2%) received pre-HIV test counseling. Of which 3407 (84.5%) received an HIV test. Eighteen (94.7%) of 19 women testing HIV-seropositive received triple-combination antiretroviral (ARV) medication. Fifteen HIV-exposed infants were delivered during the study. One infant tested HIV positive and is on ARV medication. Conclusion: Acceptance for HIV testing was high among women who received pretest counseling. An increase in the number of counselors may improve the rates of HIV testing. Follow-up mechanisms targeting mother–baby pairs should focus on increasing timely service uptake in the public sector.